Lifestyle and aerobic fitness in young volleyball athletes - Candra Dewi Ratna; Supriyanto Catur; Ivano Avandi Raymond; Nurmaya Ika (BIO Web of Conferences)
Background: The performance of volleyball athletes is influenced by aerobic fitness. Objective: This study aims to analyze factors related to aerobic fitness in volleyball athletes. Method: The research design used was a cross-sectional study. The sample consisted of 41 volleyball athletes from the Sidoarjo Indonesian Volleyball Development Club aged 14-18 years. Smoking habits and rest adequacy were measured using questionnaires, physical activity was evaluated using the Global Physical Activity Questionnaire (GPAQ), and aerobic fitness was assessed using the Multistage Fitness Test (MFT). Results: There is a significant relationship between aerobic fitness with physical activity (r=0.39, p=0.01), gender (r=- 0.76, p=0.00), and smoking habits (r=-0.35, p=0.03) in volleyball athletes. Conclusions: These findings highlight the importance of these factors in maintaining and improving aerobic fitness levels in volleyball athletes.